Flow mechanisms in the face-centred cubic micellar gel of a diblock copolymer - Castelletto, V.; Hamley, I. W.; Yang, Z. (Colloid and polymer science, 2001)
The mechanisms of flow of a face-centred cubic micellar phase were investigated using small-angle X-ray scattering (SAXS) for samples under either steady or oscillatory shear in two different geometries: Couette cell and planar shear sandwich. The system studied was a gel formed by a poly(oxyethylene)-poly(oxypropylene) diblock copolymer in water. SAXS indicated that under steady shear in a Couette cell, flow occurs via sliding of hexagonal close-packed (hcp) layers with a close-packed [110] direction along the shear direction. Under oscillatory shear in the planar shear sandwich, coexistence between this orientation and one in which the hcp layers are rotated by 30° (and flow is in a [211] direction) was observed; however, when subject to oscillatory shear in the Couette cell, flow only occurred along a [110] direction. This observation of flow in a non-close-packed direction may be due to alignment induced by the walls of the shear sandwich.[PUBLICATION ABSTRACT]